Effect of Boron Foliar Fertilizer and Mycoseed-Cookies on the Morphological and Seeds Production of Jack Bean (Canavalia ensiformis) - Armaji, Yone; Abdullah, Luki; Karti, Panca Dewi Manu Hara; Astuti, Dewi Apri; Nahrowi, Nahrowi (AGRIVITA Journal of Agricultural Science, 2025)
This research identified the effects of foliar application of boron fertilization and arbuscular mycorrhiza in the form of cookies (Miko-SC) on the growth and seed production of Jack bean. Jack bean (Canavalia ensiformis) is a dual-purpose crop that produces seeds and green-biomass as a source of protein for human consumption and animal feed. Boron and Miko-SC significantly influences seed growth and development, and arbuscular mycorrhiza can enhance mineral uptake. This study employed four doses of boron foliar fertilizer (0, 23, 46, and 69 mg/l) and three diameters of Miko-SC (4, 5, and 6 cm). The highest values of plant height, stem diameter, and leaf size were observed in the combination of 46 mg/l boron and 5-cm Miko-SC. The highest number of leaves, pod weight, and grain weight were achieved at 23 mg/l boron combined with 6-cm Miko-SC. Conclusively, the optimal combination of boron and arbuscular mycorrhiza in the form of Miko-SC cookies significantly enhanced the growth of Jack bean, offering valuable insights into cultivation improvement as a forage and food crop.